Kōyil - Kaṇapatippiḷḷai, Ci., 1899- (Aṇtarcaṉ Māṭiniraic Caiva Kalācāra Maṉṟa Veḷiyīṭu, 1979)
Articles on the importance of Chidambaram as a pilgrimage center and the origin and modes of worship in temples and a short biography of Saivite saints.